Routine analysis of sexual assault cases in Brasília, Brazil, using 23 Y chromosomal markers. (December 2015) - Ferreira, Samuel T.G.; Paula, Karla A.; Maia, Flávia A.; Svidizinski, Arthur E.; Amaral, Marinã R.; Diniz, Silmara A.; Siqueira, Maria E.; Moraes, Adriana V.; Gusmão, Leonor; Roewer, Lutz
Abstract: In sexual-assault cases, the use of DNA databases may be decisive in identifying perpetrators. Particularly, the analysis of Y chromosome STRs may play a crucial role in the study of the male portion in (i) male/female cell mixtures, (ii) mixed DNA profiles from more than one perpetrator, or from perpetrators and the sexual partners (iii) and azoospermic or oligospermic perpetrators. The analysis of Y chromosome specific markers can be also important in the study of the geographic ancestry of male lineages. The aim of this study was to genotype samples collected from sexual-assault cases in Brasília, Brazil, using the PowerPlex Y-23 System and to construct a Y-STR database of these profiles in the Instituto de Pesquisa de DNA Forense da Polícia Civil do Distrito Federal (Forensic DNA Research Institute of the Federal District Civil Police) in Brasília, in order to aid forensic casework. A total of 650 evidentiary samples were previously typed for autosomal STRs and, using a DNA database of STRs profiles of biological evidence from sexual assaults, we found 78 serial rapists who attacked 223 women in Brasília. In this work, we analyse 420 complete 23 Y-STR profiles (haplotypes) and we present the results of Y-STR analysis in sexual-assault cases. To assess the substructure of Brazilian populations we conducted Analysis of Molecular Variance (AMOVA) on different Brazilian population groups. The use of a 23 Y-STR DNA database and of an autosomal STR DNA database of samples from sexual assaults in a dual approach of a combined autosomal/Y chromosomal STR analysis played an important role in identifying perpetrators and serial rapists, highlighting the importance of its use in the investigation of sexual assaults.